2015
DOI: 10.1021/acs.orglett.5b03145
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Cucurbit[n]uril Dendrimers

Abstract: The synthesis of acyclic cucurbit[n]uril dendrimers G1 – G3 that bear four dendrons on their aromatic sidewalls via thiolate SN2 chemistry is reported. G1 – G3 are polycationic and can bind to pEGFP plasmid DNA as shown by dynamic light scattering (DLS), gel electrophoresis, and scanning electron microscopy (SEM). The gene delivery ability of G1 – G3 is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Therefore, the intervention of CB[7] can help reduce the side effects of PEI, and it will not affect the efficiency of gene delivery. In addition, Sigwalt et al also proposed that dendrimer gene vectors consisting of acyclic CB derivatives can display higher gene transfection rates …”
Section: Applications Of Cb Homologuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the intervention of CB[7] can help reduce the side effects of PEI, and it will not affect the efficiency of gene delivery. In addition, Sigwalt et al also proposed that dendrimer gene vectors consisting of acyclic CB derivatives can display higher gene transfection rates …”
Section: Applications Of Cb Homologuesmentioning
confidence: 99%
“…In addition, Sigwalt et al also proposed that dendrimer gene vectors consisting of acyclic CB derivatives can display higher gene transfection rates. 173 Therefore, CB has potential value in improving gene transfection efficiency and providing targeted gene therapy, representing a new method in this regard.…”
Section: Applications Of Cb Homologuesmentioning
confidence: 99%
“…Based on this observation, we recently prepared cationic acyclic cucurbit[n]uril dendrimers and demonstrated their ability to bind to and compact plasmid DNA although, unfortunately, gene transfection ability was quite modest. 28 Previous supramolecular researchers have shown that polycationic receptors are capable of recognizing nucleotide anions in aqueous solution due to electrostatic and other non-covalent interactions. 29 Within the CB[n] field, bambusurils and related compounds are known to be potent receptors for anions in water.…”
Section: Introductionmentioning
confidence: 99%